'Catalyst data': perverse systemic effects of audit and accountability in Australian schooling - Lingard, Bob; Sellar, Sam (Journal of education policy, 2013)
This paper examines the perverse effects of the new accountability regime central to the Labor government's national reform agenda in schooling. The focus is on National Assessment Program - Literacy and Numeracy (NAPLAN) results that now act as 'catalyst data' and are pivotal to school and system accountability. We offer a case study, with two embedded units of analysis, in which NAPLAN has become high stakes testing for systems. The first involves the relationships between the federal government and three States (Victoria, New South Wales and Queensland) in negotiating performance targets on NAPLAN for reward payments in respect of a national agreement to improve literacy and numeracy. We show how Victoria used 2009 data as baseline, set ambitious targets and failed to meet them, while Queensland set much less ambitious targets, met them and was rewarded. New South Wales created targets that combined literacy and numeracy scores, obfuscating the evidence, and met their targets. The second focuses specifically on Queensland and the ramifications of the poor performance of the State on the 2008 NAPLAN. This resulted in a review commissioned by the Premier, a Report on how to improve performance, and the introduction of Teaching and Learning Audits and State-wide targets for improvement on NAPLAN. This unit of analysis focuses on the perverse effects of this highly politicized agenda. This paper shows how States seek to protect their 'reputational capital' and as such, 'game' the system. The data for the analysis draw upon interviews with relevant senior policy-makers and on analysis of relevant documents and media coverage.